Deep brain stimulator artifact in needle electromyography: Effects and distribution in paraspinal and upper limb muscle. Issue 4 (5th March 2013) - Nandedkar, Sanjeev D.; Sheridan, Christopher; Bertoni, Sherell; Hiner, Bradley C.; Barkhaus, Paul E.
<x xml:space="preserve">Abstract</x> Introduction: Deep brain stimulators (DBS) have become a more widespread treatment option for individuals with centrally mediated movement disorders. Such devices are expected to create artifact in standard needle electromyographic (EMG) recordings. Methods: Five subjects with DBS were studied with standard concentric needle electrode EMG in paraspinal and upper limb muscles. Results: All subjects showed EMG artifact directly related to, and corresponding with, the DBS unit settings. The artifact was very prominent in all paraspinal muscles, although the amplitude was less in lumbar compared with cervical levels. With a large ground electrode next to the insertion site, the artifact was sufficiently small to allow standard EMG examination of upper limb muscles. Conclusions: The DBS artifact is so prominent in paraspinal muscles that it will not allow standard EMG examination for diagnostic purposes such as radiculopathy. The artifact itself can easily be distinguished from pathological insertional and spontaneous activity. Muscle Nerve, 2013